Pengaruh Penggunaan Fly Ash Sebgai Bahan Pengganti Sejumlah Semen dan Bahan Tambahan Terhadap Kuat Tekan pada Self Compacting Concrete (SCC) - Sahast, Corry Jayaputri; Noorhidana, Vera Agustriana; Irianti, Laksmi; Sebayang, Surya (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2022)
Self Compacting Concrete (SCC) is an innovation of concrete which has an ability to flow on its own to fill the empty voids between reinforcement and formwork without support of compaction equipment to obtain its optimum compaction. In this research, concrete cylinder with dimension of 15 cm for diameter and 30 cm for height were used as a specimen and mixed with fly ash type C as cement partial substitute material and additional substance by variation of 0%, 3%, 6%, 9%, and 12% with water cement ratio of 0.41. Slump flow test was perform to identify concrete flowability and workability followed by concrete compression test to identify compressive strength which was conducted at the age of 35 days and 56 days. Due to the fact that percentage variation of fly ash increment, the value of slump flow test was experiencing degradation whereas the compressive strength was increased. Nonetheless, the optimum fly ash application appeared when fly ash was applied as a cement partial substitute at variation of 3%, which provide concrete compressive strength in the amount of 35.98 MPa (35 days) and 33.68 MPa (56 days), and the value of concrete density were 2313.21 kg/m3 and 2279.66 kg/m3 , where the standard of slump flow test and T50 values had accomplished.